Gambaran Kadar Glukosa, Tekanan Darah, dan Profil Lipid pada Pasien - Hening Imawati (Jaringan Laboratorium Medis, 2020)
The Primary Clinic of UKSW is one of the FKTP BPJS Health implementing service program of chronic disease (Prolanis). Patients with screening of one time blood glucose 200 mg/dL or fasting blood sugar 126 mg/dL were included in control patients of DM prolanis. Patients with criteria of pre hypertension and hypertension 1 were included in the control patients of hypertensive prolanis. Patients with DM and hypertension may have level of high lipid profile so laboratory tests are needed to prevent complications, including cholesterol, HDL, LDL and triglycerides. Research objective to find out the description of glucose level, blood pressure, and lipid profile in patients of DM hipertension prolanis at the Primary Clinic of UKSW Salatiga. The research type was descriptive. The research data was primary data by measuring blood pressure, blood glucose levels and lipid profile. Research results normotension 16 (30,2%), pre hypertension 20 (37,70%), and first degree hypertension as many as 17 (32,10%). The glucose levels of normal blood 20 (37,74%), normal 33 (62,26%). The profile levels of normal lipid cholesterol 30 (54,72%), HDL 26 (49,06%), LDL 9 (18,98%), and triglyceride 30 (56,60%). The profile levels of abnormal lipid cholesterol 29 (45,29%), HDL 27 (50,95%), LDL 44 (83,02%), and triglyceride 23 (43,40%). The glucose levels of normal blood 20 (37,74%) in normotension 5 (9,4%), pre hypertension 8 (15,09%), and first degree hypertension as many as 7 (13,21%). Blood glucose levels normal 62,3% in normotension 11 (20,8%), pre hypertension 12 (22,64%) and first degree hypertension as many as 10 (18,87%).